Be careful what you say! – Evaluative change based on instructional learning generalizes to other similar stimuli and to the wider category. Issue 1 (2nd January 2021) - Luck, Camilla C.; Patterson, Rachel R.; Lipp, Ottmar V.
ABSTRACT: In evaluative conditioning, a conditional stimulus (CS; e.g. a neutral picture) acquires positive/negative valence if it is paired with a pleasant/unpleasant unconditional stimulus (US; e.g. a positive/negative picture). This valence generalises to other stimuli similar to the CS and to the wider CS category. Being informed that the CS will be paired with the US induces a similar change in valence (instructional learning), but it is not clear whether instructional learning would also generalise. In Experiment 1, participants were informed that one shape would be paired with pleasant and another with unpleasant images. These instructions instilled conditional valence to the CSs which generalised to different shapes from the same category (generalisation stimuli). In Experiment 2, we replicated this finding in an implicit measure using stimuli varying in perceptual features. Participants were informed that three CSs from one category (e.g. vegetables) would be paired with pleasant images and three CSs from a second category (e.g. office supplies) would be paired with unpleasant images. This instruction instilled conditional valence to the CSs which generalised to novel exemplars from the same categories. This suggests that conditional valence instilled via instructions generalises to other stimuli – a finding with implications for prejudice and racism.